PERAN KOPERASI DALAM PENINGKATAN PENDAPATAN PETANI NANAS DI NGANCAR KABUPATEN KEDIRI (Studi Kasus: Koperta Langgeng Mulyo) - Karma Bakti Dakhi; Hary Sastryawanto; Markus Patiung (Study Program of Agribusiness, Faculty of Agriculture, University of Wijaya Kusuma Surabay, 2023)
ABSTRACTThis research is entitled The Role of Cooperatives in Increasing Pineapple Farmer Income in Ngancar, Kediri Regency. This study aims to determine the effect of the role of cooperatives in increasing the income of pineapple farmers knowing the complaints experienced by farmers against cooperatives in Ngancar, Kediri Regency. The results of the analysis showed that the role of cooperatives had a significant effect in increasing pineapple farmers, namely services, provision of production facilities, and savings and loans, with 77.1% of respondents agreeing with the role of cooperatives in providing access to savings and loans for farmers. The role of cooperative services amounted to 73.5% strongly agreed with the services provided by cooperatives. The role of providing production facilities by 50% strongly agrees with the provision of production facilities in cooperatives. Simultaneous hypothesis testing (F test), and partial hypothesis test (t test) overall variables have a real effect on increasing farmers' income. This is also supported by the value of R – Square of 67.1% and Multiple – R of 81.9% which concluded that there is a strong relationship between servants, provision of production facilities, and savings and loans to increase farmers' income.Keywords: Cooperative, Cooperative Role, Pineapple Farmer's Income.ABSTRAKPenelitian ini berjudul Peran Koperasi dalam Peningkatan Pendapatan Petani Nanas di Ngancar Kabupaten Kediri. Penelitian ini bertujuan untuk mengetahui pengaruh peran koperasi dalam peningkatan pendapatan petani nanas mengetahui keluhan yang dialami petani terhadap koperasi yang ada di Ngancar, Kabupaten Kediri. Hasil analisis menunjukkan peran koperasi berpengaruh signifikan dalam peningkatan petani nanas yaitu pelayanan, penyediaan sarana produksi, dan simpan pinjam, sebesar 77,1% responden setuju terhadap peranan koperasi dalam memberikan akses simpan pinjam bagi para petani. Peranan pelayanan koperasi sebesar 73,5% sangat setuju dengan pelayanan yang diberikan koperasi. Peran penyediaan sarana produksi sebesar 50% sangat setuju terhadap penyediaan sarana produksi yang di ada di koperasi. Pengujian hipotesis secara serempak (uji F), dan uji hipotesis secara parsial (uji t) secara keseluruhan variabel berpengaruh nyata dengan peningkatan pendapatan petani. Hal ini juga didukung nilai dari R – Square sebesar 67,1% dan Multiple – R sebesar 81,9% yang disimpulkan bahwa terdapat hubungan yang kuat antara pelayan, penyediaan sarana produksi, dan simpan pinjam terhadap peningkatan pendapatan petani.Kata Kunci : Koperasi, Peran Koperasi, Pendapatan Petani Nanas.